The use vuestro in Cusco Spanish: New Data and New Study Perspectives - Dankel, Philipp (2021)
This article advances in explaining the productive use of vuestro in Cusco Spanish (Peru), based on new fieldwork data. We highlight its plural meaning and its systematic integration into the paradigm of ustedes. We analyze its discursive value for contrasting groups with each other and its social indexicality as a marker of literacy. Finally, we outline three proposals on the aspects still to be studied: (1) the diatopic diffusion of PL vuestro in other parts of the Andean region (and outside the Andes); (2) its diachronic evolution (as a result of the hybridization of the paradigms of vosotros and ustedes); and (3) the indirect effect of language contact (the contrastive use of vuestro as a compensation strategy for regionally relevant communicative categories, grammaticalized in Southern Quechua).